Performance Evaluation of Papaya Genotypes in Nepal - Chaudhary, JN; Gautam, IP; Bhusal, YR; Gotame, T (International Journal of Applied Sciences and Biotechnology, 2022)
Coordinated varietal trials (CVTs) were conducted to identify the high yielding papaya (Carica papaya L.) genotypes at different agro- climatic conditions with eight genotypes at Agriculture Research Station (ARS), Malepatan, Pokhara; Viuran, Nawalparasi and Parewatar, Dhading during 2006-2009 and seedling were transplanted at the time of October and experiment was designed in RCBD and replicated thrice. Observations were recorded on biological and socio-economic parameters and analyzed. The pooled data over year revealed that number of fruits, marketable yield, average weight and circumference of the fruits at ARS, Malepatan and marketable fruit yield and average weight of the fruit at Viuran, Nawalparasi and Parewatar, Dhading showed the highly significant differences among the tested genotypes. Days to first harvest and length of the fruits at ARS, Malepatan and days to flowering, first harvest and number of fruits per plant at Viuran, Nawalparasi and Parewatar, Dhading showed the significant differences within genotypes. While, non-significant difference was noticed under days to flowering at ARS, Malepatan. Genotypes Red Lady was found early in all location (295 days to harvest) and the highest production of the marketable fruit yield (104.22 t/ha) followed by Farm selection-1 (102.37 t/ha) and which was at par with each other. Farm selection-1 recorded in the highest number of fruits per plant (41.4), the average fruit weight (1.46 kg) followed by Red Lady (37 and 1.37 kg at ARS, Malepatan, Pokhara. Farmers and consumers preferred red Lady due to earliness, red flesh color and good storability. Int. J. Appl. Sci. Biotechnol. Vol 10(4): 221-224.